Mapping the Research Landscape of Mathematical Reasoning: A Bibliometric Study of the Last Decade - Nuria Amanda Manda; Rohati Rohati; Duano Sapta Nusantara (Journal of General Education and Humanities, 2026)
Mathematical reasoning is recognized as a core competency in mathematics education; however, a comprehensive overview of its research development and thematic evolution remains limited. This study aims to map the research landscape of mathematical reasoning over the last decade in order to identify publication trends, influential contributors, and emerging research themes. A quantitative bibliometric approach was employed using Scopus-indexed journal articles, which were analyzed and visualized through VOSviewer to examine co-authorship networks, keyword co-occurrence, and thematic evolution. The findings indicate a significant growth in publications since 2018, reflecting increasing global attention to mathematical reasoning. The results further reveal that research in this field has developed multidimensionally, integrating cognitive, pedagogical, evaluative, and contextual dimensions, with a recent shift toward assessment practices, problem-based learning, and technology-enhanced instruction. These findings confirm that mathematical reasoning has become a mature and strategically important field in mathematics education, while highlighting opportunities for further research that integrate digital innovation and deep learning-oriented approaches.